Molecular and functional characterization of a fads2 orthologue in the Amazonian teleost, Arapaima gigas - Lopes-Marques M. (2017)
The Brazilian teleost Arapaima gigas is an iconic species of the Amazon. In recent years a significant effort has been put into the farming of arapaima to mitigate overfishing threats. However, little is known regarding the nutritional requirements of A. gigas in particular those for essential fatty acids including the long-chain polyunsaturated fatty acids (LC-PUFA) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The ability to biosynthesize LC-PUFA is dependent upon the gene repertoire of fatty acyl desaturases (Fads) and elongases (Elovl), as well as their fatty acid specificities. In the present study we characterized both molecularly and functionally an orthologue of the desaturase fatty acid desaturase 2 (fads2) from A. gigas. The isolated sequence displayed the typical desaturase features, a cytochrome b5-domain with the heme-binding motif, two transmembrane domains and three histidine-rich regions. Functional characterization of A. gigas fads2 showed that, similar to other teleosts, the A. gigas fads2 exhibited a predominant Δ6 activity complemented with some capacity for Δ8 desaturation. Given that A. gigas belongs to one of the oldest teleostei lineages, the Osteoglossomorpha, these findings offer a significant insight into the evolution LC-PUFA biosynthesis in teleosts. © 2016 Elsevier